THE DIFFERENCE OF HISTOPATHOLOGICAL IMAGE OF THE WISTAR RAT’S KIDNEY ADMINISTERED WITH GRADUAL DOSAGE OF PYRETHROID - Diaz Almayang; Saebani Saebani; Tuntas Dhanardhono; Endang Ambarwati; Ika Pawitra Miranti (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Pyrethroid pesticide poisoning cases in developed and developing countries have a high incidence every year. One of the active substances in pyrethroid widely used is cypermethrin. The effects of cypermethrin intoxication on the kidneys, especially in humans, are little to be studied. This study aims to determine the difference in the histopathological image of the Wistar rat’s kidney.Method: The experimental research of the post-test only control group design involved 24 male Wistar rats divided into 4 groups randomly, the control (not given cypermethrin), treatments of 125 mg/kgBW, 250 mg/kgBW, and 500 mg/kgBW. Cypermethrin are given orally for 14 days. After the rats were terminated, the kidney were processed to be paraffin-embedded tissues and stained with HE. Tubular injuries were examined using 400x magnification of light microscope and focused on closure of tubular lumen as well as proteinaceous cast inside the lumens.Results: The results of this study showed that the means of histopathological damage to the kidneys increased from control group to 500 mg/kgBW treatment group. Statistical analysis with One way ANOVA showed significant differences (p<0.001), continued with Post hoc games Howell test, there was a significant differences between control group with 250 mg/kgBW treatment group and 500 mg/kgBW treatment group, and between 125 mg/kgBW treatment group with 250mg/kgBW treatment group and 500 mg/kgBW treatment group. There was no significant difference between the control group with 125 mg/kgBW group and 250 mg/kgBW treatment group with 500 mg/kgBW treatment group.Conclusion: There is a significant difference in renal histopathological image due to exposure to pyrethroid (cypermethrin) in gradual doses. The image of kidney damages can result in tubules injury which include: albuminous degeneration with narrowing of the tubular lumen and hyaline cast. The means of tubular injury rate will increase with increasing dose of pyrethroid.